Company and securities laws - Zahir, M. (Dhaka : The University Press, 2000)
Compendium of company and securities laws, rules, regulations, notifications, and forms.
Includes bibliographical references (p. [909]-910).
Keywords: Corporation law -- Bangladesh; Securities -- Bangladesh